Dynamics of Immigration: Displacement & Identity Crisis in Donald R. Gallo’s From Crossing: Stories about Teen Immigrants - Dhobi, Saleem (Cognition, 2023)
The paper examines the displaced position of immigrants portrayed in the selected stories of Donald R. Gallo’s From Crossing: Stories about Teen Immigrants and explores the variables that affect the lives of the immigrants in a multicultural setting. The article analyzes psychological and physical repercussions of displacement of teenage characters in the stories with the focus on teens’ psychological status during the transition period. Teenagers undergo complexity of internal and social identities in which they face psychological complexity. They experience identity crisis in the destination country. Because of their belonging to different backgrounds, they undergo varied levels of domination and marginalization. They are not accepted and their identities are not tolerated because of being outsiders. Their movement from the homeland to the destination countries becomes a cause for being unaccepted. Their experience in the intolerant society leads them to alienation. The article has employed Stuart Hall’s perspective of identity and cultural diversity to scrutinize the displacement and identity crisis of the teenagers depicted as immigrants in the selected stories. The American society imposes established notions on the immigrants who are teenagers whose psyche is complex because of their displacement. They experience mental displacements as well in a new social setting as Lacan focuses on the teenage problem of identity when they shift from one teenage state to maturity. Moreover, it problematizes when people are culturally displaced in another culture where they have to adopt different cultures.